Systematic Theology in the Nordic Countries after 1945 - Jan-Olav Henriksen (St Andrews Encyclopaedia of Theology, 2023)
Christian systematic theologies in the Nordic countries share common traits in terms of their Lutheran heritage and the close relationship between church and state (‘folk-church’) organizations that have dominated church life and theological reasoning up until the present. Although international exchange and dialogue further afield have increased over recent decades, the influence of Luther, Kierkegaard, and Grundtvig, as well as Løgstrup and Wingren are still prominent. Systematic theology is understood here in a broad sense: comprising dogmatics, ethics, and philosophy of religion. The lines that separate these disciplines are relatively porous in the Nordic context. This article presents the distinguishing features that characterize contemporary systematic theology in the Nordic countries. Firstly, the theological ideas and work emerging from after 1945 will be explored, mainly focusing on some influential theologians. This sketch is followed by a discussion of two original contributions from Nordic theology: Scandinavian Creation Theology and the Finnish Luther interpretation. The last part gives a brief overview of selected contemporary theologians in the different countries and their fundamental orientations.